EU-China trade relations: Where do we stand, where should we go? - Alexander-Nikolai Sandkamp (Kiel Institute for the World Economy (IfW Kiel), 2024)
In the aftermath of the Covid-19 pandemic, China's share in European trade has fallen continuously. Nevertheless, the country remains the EU's largest source of imports (20.5 percent in 2023) and its third largest export destination (8.7 percent). • This apparent dominance of China is put into perspective when incorporating intra-EU trade. For example, Germany - Europe's largest economy - sent 6.1 percent of its exports to China, but 55 percent to EU members states. For imports, the Chinese and European shares are 11.5 percent and 52.7 percent, respectively. • Decoupling the EU from China (i.e. almost eliminating bilateral trade) would permanently reduce European real income by 0.8 percent in the long-run. In terms of gross domestic product in 2023, the EU would forego 136 billion EUR of value added every year. Short-term effects are likely to be stronger. • China dominates global production of important products such as laptops and mobile phones as well as raw materials including Germanium and Gallium that are critical for the green energy transition. A trade disruption might thus both delay the energy transition and increase its costs. • To reduce specific dependencies, the EU should intensify its efforts to diversify procurement by increasing the attractiveness of alternative suppliers. Finding the courage to move forward in the negotiation of free trade agreements with potential strategic partners such as Australia and the Mercosur countries would strengthen the EU's geopolitical position and increase prosperity among partners. – – Im Nachgang der Covid-19-Pandemie ist der Anteil Chinas am europäischen Handel kontinuierlich gesunken. Dennoch bleibt das Land die größte Importquelle der EU (20,5 Pro-zent im Jahr 2023) und ihr drittgrößtes Exportziel (8,7 Prozent). • Diese scheinbare Dominanz Chinas relativiert sich, wenn man den Intra-EU-Handel mit einbezieht. Deutschland - die größte europäische Volkswirtschaft - lieferte beispielsweise 6,1 Prozent seiner Ausfuhren nach China, aber 55 Prozent in die EU-Mitgliedstaaten. Bei den Einfuhren liegen die chinesischen und europäischen Anteile bei 11,5 Prozent bzw. 52,7 Prozent. • Eine Abkopplung der EU von China (d.h. ein weitgehender Wegfall des bilateralen Handels) würde das europäische Realeinkommen langfristig um 0,8 Prozent senken. Bezogen auf das Bruttoinlandsprodukt im Jahr 2023 würde die EU jährlich auf 136 Milliarden EUR an Wertschöpfung verzichten. Kurzfristig dürften die Auswirkungen stärker sein. • China dominiert die weltweite Produktion von wichtigen Produkten wie Laptops und Mobiltelefonen sowie von Rohstoffen wie Germanium und Gallium, die für die grüne Energiewende entscheidend sind. Eine Handelsunterbrechung könnte daher sowohl die Energiewende verzögern als auch deren Kosten erhöhen. • Um spezifische Abhängigkeiten zu verringern, sollte die EU ihre Bemühungen um eine Diversifizierung der Beschaffung verstärken, indem sie die Attraktivität alternativer Lieferanten erhöht. Den Mut zu finden, die Verhandlungen über Freihandelsabkommen mit potenziellen strategischen Partnern wie Australien und den Mercosur-Ländern voranzutreiben, würde die geopolitische Position der EU stärken und den Wohlstand aller Beteiligten erhöhen.
Keywords: 330; China; European Union; Germany; international trade; decoupling; China; Europäische Union; Deutschland; internationaler Handel; Entkopplung